O trabalho dos assistentes sociais nas organizações não governamentais (ONGs): uma análise a partir da conjuntura de crise do capitalismo contemporâneo - Medeiros, Najara Sousa (2017)
The present Master's Dissertation, entitled "The Work of Social Workers in NonGovernmental Organizations (NGOs): an analysis based on the crisis situation of contemporary capitalism" is part of the Social Work, Social Work and PPGSS / UFPB. It presents as an object of study the analysis of the main influences of the crisis of contemporary capitalism and the consequent neoliberal offensive in the work of social workers from the work of these professionals in Non Governmental Organizations (NGOs). The context of these organizations is one of the sociooccupational spaces of Brazilian social workers, whose performance is not effective in meeting the social demands from the perspective of the defense of rights. This investigative study was referenced in Marxist critical social theory based on dialectical historical method in the development of field research, bibliographical and documentary research. Field research was conducted in 06 (six) Non-Governmental Organizations (NGOs) of João Pessoa / PB, being: Association of Disabled and Relatives (ASDEF); Small House David; Cunha Feminist Collective Association; Legion of Good Will (LGW); Institute of the Blind "Adalgisa Cunha" and the Donos do Amanhã Association. The collection of primary data was carried out with 10 (ten) Social Service professionals working in these NGOs in the year 2016. Methodologically, instruments and techniques of a quantitative and qualitative nature were used in the collection and analysis phases of the data. To collect data, we used the semi-structured interview that allowed the direct contact between researcher and research subjects, as well as the use of the field diary to record the non-systematic observations, besides the documentary and bibliographic survey. In the data analysis phase, we applied: a) for the closed questions, the descriptive statistical discussion with the simple and graphic tabular reading, in addition to tables; B) for open questions, the use of content analysis by thematic categorization, among other methodological procedures. The relevance of the research referred to herein lies in the attempt to deepen the debate and contribute to the production of knowledge about the unfolding of the crisis of contemporary capitalism in the scope of social policies, as well as to analyze the impacts on the work of Social Service professionals inserted in NGOs.Conclusively, it is evident that the contribution of this critical research on the work of the Social Worker in NGOs, was based on the professional skills and abilities directly associated to the elaboration, implementation, and evaluation of the social policies, directly or (Law No. 8.662 / 93), with a view to building a corporate project in which the political culture of a more just and egalitarian society predominates.